Rationality and self-interest as economic-exchange strategy in borderline personality disorder: game theory, social preferences, and interpersonal behavior - Jeung, Haang; Schwieren, Christiane; Herpertz, Sabine (Neuroscience & biobehavioral reviews, 2016)
Borderline Personality Disorder (BPD) is characterized by severe and persistent impairments in interpersonal functioning. Given the complexity of social interactions, studying the interactive behavior of BPD patients is challenging. One way to implement both tight experimental control and realistic, externally valid settings is to use game-theoretical experiments. This review discusses findings from economic exchange studies in BPD against the background of game-theoretical literature. BPD patients do not seem to derive utility from mutual cooperation with others and appear not to “forgive” a partner’s unfairness. By pursuing a strategy of negative reciprocity, BPD patients seem to act mostly “rationally” and in their own self-interest. Their “grim trigger strategy” resembles the theoretical ideal of the rational and self-interested agent homo economicus. Finally, we summarize how research findings from economics and clinical psychiatry may be mutually enriching and propose new research ideas in this fascinating field.
Gesehen am 25.10.2017